Migrations of theory, method and practice: a reflection on themes in migration studies (Review article) - Ingrid Palmary (Psychology in Society)
In this review article, I offer some reflection on three themes in migration research, namely, the categorisation and quantification of migration, the role of trauma and distress in such categorisation, and the feminisation of migration. I was prompted to explore these three themes after reading a recent publication on migration in southern Africa (edited by Kok, Gelderblom, Oucho and Van Zyl, 2006). In this paper I raise these as three areas that appear to be determining the boundaries of the discipline of migration studies in ways that raise familiar concerns about representation, claims to objectivity and the perpetuation of inequalities. Although these are by no means new debates in the social sciences, they are ones that appear to have been excluded from migration studies in southern Africa with worrying implications for the role that the discipline can play in the repressive management of migration.